2018
DOI: 10.21815/jde.018.036
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of U.S. Dental Students’ Experiences with International Service Trips

Abstract: Globalization, along with the increasing prevalence of non-communicable diseases, their risk factors, and poor oral health, demands global approaches to oral health care. Trained health care workers' providing volunteer services abroad is one model used for improving access to dental services for some communities. Currently, little is known about U.S. dental student involvement in international clinical service volunteerism. The aim of this exploratory study was to capture national survey data from predoctoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 26 publications
2
43
1
Order By: Relevance
“…It should also be noted that though the vast majority of literature related to burnouts in health care students is derived from studies in the field of medicine, similar stressful behaviors have also been reported in dental (Lambert et al, 2018;Pape et al, 2018), pharmacy (Nuffer et al, 2017;Lysak et al, 2018;Tetenbaum-Novatt et al, 2018), and nursing students (Sun et al, 2016;Beanlands et al, 2019;Valero-Chillerón et al, 2019). The common reasons for burnouts in these students also include an academic overload (Pape et al, 2018;Queen and Hess, 2018;Dames, 2019), unfamiliar working situations (Hennessy et al, 2016;Bing-You et al, 2018;Budu et al, 2019), and fear of making mistakes with patients (Bronson, 2016;Worly et al, 2018;Riley et al, 2019).…”
Section: Challenges Of Present-day Health Care Educationmentioning
confidence: 80%
See 4 more Smart Citations
“…It should also be noted that though the vast majority of literature related to burnouts in health care students is derived from studies in the field of medicine, similar stressful behaviors have also been reported in dental (Lambert et al, 2018;Pape et al, 2018), pharmacy (Nuffer et al, 2017;Lysak et al, 2018;Tetenbaum-Novatt et al, 2018), and nursing students (Sun et al, 2016;Beanlands et al, 2019;Valero-Chillerón et al, 2019). The common reasons for burnouts in these students also include an academic overload (Pape et al, 2018;Queen and Hess, 2018;Dames, 2019), unfamiliar working situations (Hennessy et al, 2016;Bing-You et al, 2018;Budu et al, 2019), and fear of making mistakes with patients (Bronson, 2016;Worly et al, 2018;Riley et al, 2019).…”
Section: Challenges Of Present-day Health Care Educationmentioning
confidence: 80%
“…Other student cohorts have also reported that retrieval practices were especially helpful in tests that required the integration of both short-answer and context-rich multiple-choice questions (Bradley et al, 2012;Rosenkranz et al, 2015;Augustyniak et al, 2016;Baig and Mallu, 2017). It has also been observed that repeated retrieval testing of medical and nursing procedures enhanced motor skill retention over long periods of time in these students (Lambert et al, 2018;Chuenjitwongsa et al, 2018a).…”
Section: Identify and Nurture The Learning Efforts Of Health Care Stumentioning
confidence: 98%
See 3 more Smart Citations